2007
DOI: 10.2300/acari.16.129
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Neoseiulus californicus (Acari: Phytoseiidae) on citrus in Kyushu district, Japan.

Abstract: Neoseiulus californicus has been increasing in number and geographical distribution since the 1990s in Japan, and is considered to be a new prospective predator species against Panonychus citri on citrus. We investigated the occurrence of N. californicus in citrus orchards with different agrochemical spraying programs in Kyushu district, south-western Japan. The occurrence of N. californicus greatly differed among orchards. In conventional control orchards and agrochemical-reduced orchards, N. californicus fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…For A. pelekassi, Ashihara et al (2004) showed that juveniles of A. eharai and N. womersleyi could not utilize it as food for development. The present study showed that P. nipponicus could utilize A. pelekassi as food for development and reproduction, but A. pelekassi was inadequate food for the other species, including A. eharai and N. californicus, which are dominant species in citrus orchards in Japan (Katayama et al, 2006;Kishimoto et al, 2007;Miyashita et al, 2014;Miyazaki et al, 2012). This result suggests that the conservation of A. eharai or N. californicus on citrus is ineffective for the control of A. pelekassi.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…For A. pelekassi, Ashihara et al (2004) showed that juveniles of A. eharai and N. womersleyi could not utilize it as food for development. The present study showed that P. nipponicus could utilize A. pelekassi as food for development and reproduction, but A. pelekassi was inadequate food for the other species, including A. eharai and N. californicus, which are dominant species in citrus orchards in Japan (Katayama et al, 2006;Kishimoto et al, 2007;Miyashita et al, 2014;Miyazaki et al, 2012). This result suggests that the conservation of A. eharai or N. californicus on citrus is ineffective for the control of A. pelekassi.…”
Section: Resultsmentioning
confidence: 61%
“…On the other hand, P. nipponicus has not been recorded on citrus (Katayama et al, 2006;Kishimoto et al, 2007;Miyashita et al, 2014;Miyazaki et al, 2012). Therefore, for the utilization of P. nipponicus, it should be necessary to develop methods for establishment and maintaining P. 5.67 (1) 3.56 ± 0.14 (6) 16.7 (12) 9.00 ± 0.33 (2) 0.25 ± 0.18 (12) Tea pollen 97.8 (46) 3.17 ± 0.09 (18) 2.86 ± 0.09 (27) 88.2 (17) 1.87 ± 0.10 (15) 17.29 ± 1.80 (17) E. sojaensis A. pelekassi (12) 3.76 ± 0.72 (7) 1.33 ± 0.72 (12) Tea pollen …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is also the dominant phytoseiid species in conventionally managed citrus orchards in Shizuoka Prefecture, Ehime Prefecture, and the Kyushu District in central to southwestern Japan, and serves as an effective predator of the dominant spider mite species, P. citri, on citrus trees (Katayama et al, 2006;Ohnishi et al, 2006;Kishimoto et al, 2007). Therefore, conservation of this species for the biological control of P. citri in citrus orchards will likely be quite beneficial; however, little is known about the overwintering behavior of this species in the field (e.g., Hart et al, 2002, for winter mortality), although several physiological studies have examined its winter hardiness (e.g., diapause propensity and cold tolerance; Castagnoli et al, 1996;Jolly, 2000;Hart et al, 2002;Gotoh et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This species is at present distributed throughout Japan, except northern areas (Ehara and Gotoh, 2009), dominating some citrus, apple, and peach orchards (Mochizuki et al, 2005;Katayama et al, 2006;Ohnishi et al, 2006;Kishimoto et al, 2007). The region where N. californicus is distributed in Japan partially overlaps in latitude with the fruitgrowing areas of mainland Korea; therefore, there is a possibility that N. californicus can overwinter on mainland Korea.…”
Section: Discussionmentioning
confidence: 99%